The Changing Landscape of Naive T Cell Receptor Repertoire With Human Aging - Egorov, Evgeny S.; Kasatskaya, Sofya A.; Zubov, Vasiliy N.; Izraelson, Mark; Nakonechnaya, Tatiana O.; Staroverov, Dmitriy B.; Angius, Andrea; Cucca, Francesco; Mamedov, Ilgar Z.; Rosati, Elisa; Franke, Andre; Shugay, Mikhail; et al. (Frontiers in Immunology, 2018)
Human aging is associated with a profound loss of thymus productivity, yet naïve T lymphocytes still maintain their numbers by division in the periphery for many years. The extent of such proliferation may depend on the cytokine environment, including IL-7, and T-cell receptor (TCR) “tonic” signaling mediated by self pMHCs recognition. Additionally, intrinsic properties of distinct subpopulations of naïve T cells could influence the overall dynamics of aging-related changes within the naïve T cell compartment. Here we investigated the differences in the architecture of TCR beta repertoires for naïve CD4, naïve CD8, naïve CD4+CD25-CD31+ (enriched with recent thymic emigrants, RTE), and mature naïve CD4+CD25-CD31- peripheral blood subsets between young and middle-age/old healthy individuals. In addition to observing the accumulation of clonal expansions (as was shown previously), we reveal several notable changes in the characteristics of T cell repertoire. We observed significant decrease of CDR3 length, NDN insert and number of non-template added N nucleotides within TCR beta CDR3 with aging, together with a prominent change of physicochemical properties of the central part of CDR3 loop. These changes were similar across CD4, CD8, RTE-enriched, and mature CD4 subsets of naïve T cells, with minimal or no difference observed between the latter two subsets for individuals of the same age group. We also observed an increase in “publicity” (fraction of shared clonotypes) of CD4, but not CD8 naïve T cell repertoires. We propose several explanations for these phenomena built upon previous studies of naïve T-cell homeostasis, and call for further studies of the mechanisms causing the observed changes and of consequences of these changes in respect of the possible wholes formed in the landscape of naïve T cell TCR repertoire.